Pengaruh Faktor Internal terhadap Dampak Mental Santri - Zahro, Fatimatuz (Journal of Islamic Education Counseling, 2022)
The purpose of this study is to find out what internal factors affect the mental health of students. The case study in this case is bullying that occurs in Islamic boarding schools. The research subjects were 10 students from various different Islamic boarding schools in Buntet Pesantren, Cirebon. The approach used is Focus Group Discussion (FGD). Analysis of the data used is a qualitative research method. The results showed that the internal factors that influenced the mental health of students from bullying include innate factors that already have feelings of discouragement, emotions that are still unstable, less able to adapt and socialize, psychological factors, low self-confidence, and a personality that is weak. tend to be closed.